تنكو محمد حسبي الصديقي وجهوده في تطوير الفقه الأسلامي في أندونيسيا - Muhammad Iqbal Kilwo (Universiti Sains Islam Malaysia, 2024)
Thesis (M.A) - Faculty of Shariah and Law, Universiti Sains Islam Malaysia, 2012.